Բոլշևիզմը որպես կարգի նախագիծ - Բաբերովսկի, Յորգ (YSU Journal of International Affairs, 2018)
A number of features of Bolshevism are considered in the article. Taking into account the fact that the 20th century was the stage of the illusion of the realization of order. Accordingly, the world is just a will and understanding, and therefore it can somehow be regulated or changed. Realizing the surrounding world as a challenge and trying to subordinate their will, people realize their destiny. Now they know that any order is possible, if it was ever thought, and if there are tools that can be transferred to the world. Without a military presence of the Soviet occupation forces and the regulating role of the Eastern bloc, there would be no peaceful change of power. The Soviet Union entered the European reality as a power project but withdrew from the scene as a peacemaker.
Keywords: bolshevism, public order, heritage, utopia, communist, marxist, Soviet Union